Use some probability amputated models to study the characteristics of health payments in the Iraqi Insurance Company - خماس, قيس سبع; عبد الله, ثائرة نجم (Journal of Economics and Administrative Sciences, 2013)
AbstractDue to the lack of previous statistical study of the behavior of payments, specifically health insurance, which represents the largest proportion of payments in the general insurance companies in Iraq, this study was selected and applied in the Iraqi insurance company.In order to find the convenient model representing the health insurance payments, we initially detected two probability models by using (Easy Fit) software:First, a single Lognormal for the whole sample and the other is a Compound Weibull  for the two Sub samples (small payments and large payments), and we focused on the compound model in some detail in terms of drafting and its importance. With the application of the state of amputation in both the fact that the specific health payments from the top by two million diners in this company.Both models Parameters were estimated using the maximum likelihood method (MLE) and the use of style (Newton - Raphson) to find these estimates. And then compare between models using standard (MSE). Was reached in general that the compound model is better than a single model in the representation of payments.